Challenges in mucosal vaccines for the control of infectious diseases. (9th June 2014) - Azegami, Tatsuhiko; Yuki, Yoshikazu; Kiyono, Hiroshi
Abstract : Mucosal vaccines for the control of infections Abstract: The mucosal surface is the largest route through which pathogens enter the human body. To control the outbreak of mucosal infectious diseases, we must use our knowledge of the mucosal immune system to create vaccines that elicit protective mucosal and systemic immunity. Mucosal vaccines have advantages over traditional injectable vaccines in that they not only induce effective mucosal immune responses, but they also do not cause physical or psychological discomfort. Mucosal vaccines currently licensed for human use include oral vaccines against Vibrio cholerae, Salmonella typhi, poliovirus and rotavirus, and nasal vaccines against influenza virus. To further improve the existing vaccines, it will be necessary to develop novel vaccine production, storage and delivery systems through innovative strategies derived from interdisciplinary scientific research. Our accumulated knowledge of the innate and acquired arms of the mucosal immune system and the recent scientific and technical advancements in the fields of molecular biology, plant biology, bio-engineering and chemical engineering, genome biology and systems biology have created a unique research and development platform for the development of the next generation of mucosal vaccines. This review summarizes the current perspectives and future directions of mucosal vaccine development with emphasis on oral and nasal vaccines for the control of infectious diseases.